2006
DOI: 10.1111/j.1468-005x.2006.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

BPR implementation in Europe: the adaptation of a management concept

Abstract: This paper analyses Business Process Re-engineering (BPR)implementation in 20 European firms. In contrast with the radical postulates of the early orthodox literature, the findings reveal that BPR was used in a preventive way, with implementation time lengths directly related to the scope of the organisational changes attempted and generating moderately positive results according to corporate performance indicators, with relatively low social cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…A second major research theme is outcome, the organisational benefits that businesses achieve by taking a processes-oriented view of organisational improvement (Gulledge & Sommer, 2002;Kohlbacher, 2010;Larsen & Myers, 1997;Mansar & Reijers, 2007). Although early researchers argue that firms should strive for radical changes with dramatic effects on productivity and costs (Hammer & Champy, 1993), current research has found that most projects find the radical approach too challenging, and therefore realise more modest benefits (Albizu & Olazaran, 2006;Grover et al, 1995), whether effectiveness or efficiency gains.…”
Section: Total Quality Managementmentioning
confidence: 98%
“…A second major research theme is outcome, the organisational benefits that businesses achieve by taking a processes-oriented view of organisational improvement (Gulledge & Sommer, 2002;Kohlbacher, 2010;Larsen & Myers, 1997;Mansar & Reijers, 2007). Although early researchers argue that firms should strive for radical changes with dramatic effects on productivity and costs (Hammer & Champy, 1993), current research has found that most projects find the radical approach too challenging, and therefore realise more modest benefits (Albizu & Olazaran, 2006;Grover et al, 1995), whether effectiveness or efficiency gains.…”
Section: Total Quality Managementmentioning
confidence: 98%
“…Studies shows that the objectives of BPR are very clear and it covers all the aspects of business needs e.g. increasing revenues (Eisner, 2000), dramatic changes in profits and market share (Knights and Willmott, 2000), improving quality of customer service (Ranganathan and Dhaliwal, 2001), induction of new products and services (Choi, 1995), reducing operating cost (Knights andWillmott, 2000, Maglitta, 1995), streamlining operations (Colin and Coulson, 1997), meeting client's demands (Albizu and Olazaran, 2006), and to overcome crises situation (Hammer and Stanton, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, research by critical scholars (Adler and Cole, 1993;Vidal, 2007a) demonstrates there are many forms of non-value added activities that can be identified and eliminated -inefficient layouts and process flows, bottlenecks, slow machine changeovers and so on -without resorting to work intensification. Further, it has been shown in a range of private and public sector contexts (Adler and Cole, 1993;Albizu and Olazaran, 2006;Blair et al, 1998;Kochan et al, 1997;Leverment et al, 1998;Stanton et al, 2014;Vidal, 2007b) that reengineering and lean can be implemented to include true multi-skilling and substantive employee involvement -even if such outcomes are the small minority of cases.…”
Section: Introductionmentioning
confidence: 99%